2013
DOI: 10.1051/0004-6361/201322716
|View full text |Cite
|
Sign up to set email alerts
|

A Sino-Germanλ6 cm polarisation survey of the Galactic plane

Abstract: Aims. Information of small-diameter sources is extracted from the Sino-German λ6 cm polarisation survey of the Galactic plane carried out with the Urumqi 25-m telescope. Methods. We performed two-dimensional elliptical Gaussian fits to the λ6 cm maps to obtain a list of sources with total-intensity and polarised flux densities. Results. The source list contains 3832 sources with a fitted diameter smaller than 16 and a peak flux density exceeding 30 mJy, so about 5× the rms noise, of the total-intensity data. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…1. Archival data were taken from Reich et al (1984); Sieber & Seiradakis (1984); Caswell et al (1985); Reich et al (1990); Becker et al (1991); Taylor et al (1992); White & Becker (1992); Hurley-Walker et al (2009); Sun et al (2011);Reich et al (2014). Manchester et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1. Archival data were taken from Reich et al (1984); Sieber & Seiradakis (1984); Caswell et al (1985); Reich et al (1990); Becker et al (1991); Taylor et al (1992); White & Becker (1992); Hurley-Walker et al (2009); Sun et al (2011);Reich et al (2014). Manchester et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To identify H ii regions in the Sino-German λ6 cm survey, we separated the Urumqi λ6 cm sources into two groups: smalldiameter sources from Reich et al (2014) and extended sources (apparent size > 16 ′ ) that have not been catalogued yet. In this work, we only consider H ii regions whose boundaries and flux densities can be reliably determined by the Urumqi data.…”
Section: Methodology: Identification Of H II Regionsmentioning
confidence: 99%
“…Descriptions of a detailed system set-up and data reduction can be found in Sun et al (2006Sun et al ( , 2007 and Gao et al (2010). From the λ6 cm survey, Reich et al (2014) identified 3 832 3 small-diameter sources with apparent sizes of less than 16 ′ via two-dimensional elliptical Gaussian fits. The fitted major and minor axes were recorded together with the position angles with respect to the north Galactic pole.…”
Section: Urumqi λ6 CM Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(1) where q(r, p, t) is the acceleration sources, ψ(r, p, t) is the density of CR particles per unit momentum p at position r, V c is the convection velocity, ṗ ≡ dp/dt is momentum loss rate, τ f and τ r are the characteristic time scales for fragmentation and radioactive decay respectively; D xx and D pp are the diffusion coefficients in coordinate and momentum space respectively. (5,30-31) 1 (Smith et al 1994);2 (Gorham et al 1996);3 (Mavromatakis et al 2002);4 (Xiao et al 2009);5 (Green 2014);6 (Kothes et al 2006);7 (Kothes et al 2008);8 (Blair et al 2005);9 (Sun et al 2006);10(Yar-Uyaniker et al 2004);11 (Reich et al 2014);12 (Joncas et al 1989);13 (Leahy & Tian 2006);14 (Reich et al 1992);15 (Yamauchi et al 2000);16 (Xu et al 2007);17 (Katsuda et al 2009);18 (Reich et al 2003);19 (Leahy & Tian 2007);20 (Plucinsky et al 1996);21 (Brisken et al 2003);22 (Cha et al 1999);23(Alvarez et al 2001);24 (Caraveo et al 2001);25 (Miceli et al 2008);26(Aschenbach 1998);27 (Iyudin et al 1998);28 (Redman & Meaburn 2005);29 (Katsuda et al 2008);30 (Lazendic et al 2004);31 (Morlino et al 2009).…”
Section: Model Descriptionmentioning
confidence: 99%